HUBUNGAN LINGKAR PERUT DENGAN KEJADIAN PREDIABETES DI POSBINDU PTM UPTD PUSKESMAS SIPEA PEA - K.SIMAMORA, YENNI CRARISZA; NASUTION, YULIA AFRINA (LP2MTBM MAKARIOZ, 2023)
The health of the world is now being affected by obesity. The excessive buildup of fat that results from a long-term mismatch between caloric intake and energy expenditure is known as obesity. Obesity is deemed to exist if the body mass index (BMI) is more than 30 kg/m2. Increased visceral fat is linked to metabolic disorders, which can worsen insulin sensitivity and glucose tolerance, raising blood sugar levels. Prediabetes, which will eventually lead to diabetes mellitus, is a risk factor for this illness. Impaired glucose tolerance or impaired fasting blood sugar levels are symptoms of prediabetes.incidence of prediabetes in the working area of the UPTD Sipea pea Health Center. The purpose of this study was understanding the connection between abdominal circumference and the prevalence of prediabetes in the UPTD Puskesmas Sipea pea work region. The research method utilized is descriptive analytic research, and the cross-sectional study research design is employed, where the researcher only studies the subject once at a certain time. This study was carried out in Posbindu PTM UPTD Sipea Pea in the Central Tapanuli Regency of North Sumatra's West Sorkam District. The result at This study according to the results of the Spearman test, 50 respondents met the criterion for prediabetes, with 11 respondents having a percentage of 22% and 39 respondents having a percentage of 78%. P-value = 0.041. The conclusion here is a correlation between belly circumference and the prevalence of prediabetes at the UPTD Sipea pea Health Center